The impact of South Korean gastrodiplomacy in Indonesia on the development of Korean food business opportunities in Indonesia (Tamalanrea: Journal of Government and Development (JGD), 2024)
This article explores how South Korean gastrodiplomacy fosters Korean food business opportunities in Indonesia. Gastrodiplomacy, a soft diplomacy approach, uses cultural elements like cuisine to enhance bilateral relations and national image. South Korea has effectively leveraged the Korean Wave—a global phenomenon including music, drama, food, and lifestyle—to introduce its cuisine to international audiences, including Indonesia. The study outlines the historical and technological developments that spread Korean culture in Indonesia, leading to increased interest in Korean language, entertainment, and culinary experiences. Using qualitative methods like literature reviews and document analysis, it examines the impact of Korean culture on Indonesian society and the resulting business opportunities for Korean food. The article underscores the role of soft power in promoting cultural exchange and attracting Indonesian consumers to Korean cuisine. South Korean gastro diplomacy's success is evident in the rise of Korean restaurants and food stalls in Indonesia, catering to both Korean culture fans and the general public. However, challenges such as differing culinary preferences, limited access to authentic ingredients, cultural eating habits, pricing issues, and promotional strategies are identified as potential obstacles to expanding Korean food businesses in Indonesia. The study provides insights into how cultural diplomacy can create economic opportunities and enhance international cooperation by analyzing gastro diplomacy and its implementation through the Korean Wave. The findings suggest that strategic collaboration between the South Korean government and local stakeholders is essential to overcoming barriers and maximizing gastro diplomacy's benefits for both nations.